Toxicity of the venom of Latrodectus (Araneae: Theridiidae) spiders from different regions of Argentina and neutralization by therapeutic antivenoms - de Roodt, Adolfo R. (2017)
Fil: de Roodt, Adolfo Rafael. ANLIS Dr.C.G.Malbrán. Instituto Nacional de Producción de Biológicos. Servicio antígenos y antisueros; Argentina.